Peran Media Sosial dalam Membentuk Gaya Bahasa dan Identitas Pengguna di Era Digital - Ahmad Malik Pratama; Siti Nurhaliza; Andrianto Ahmad Susanto (Journal of Language Studies, 2026)
Social media has become a dominant platform influencing language use and identity construction in the digital era. This study aims to analyze the role of social media in shaping users’ language styles and identities through a sociolinguistic perspective. The research employs a qualitative descriptive method by examining discourse patterns across social media platforms and reviewing relevant scholarly literature. Data were collected through document analysis of previous studies and digital communication samples, focusing on language variation, slang usage, and identity representation. The findings reveal that social media significantly contributes to linguistic innovation, including the emergence of slang, abbreviations, and multimodal expressions such as emojis and memes. Furthermore, users construct multiple identities through language choices influenced by social context, audience, and platform norms. The study also identifies challenges, such as language simplification and the erosion of formal language structures. This research highlights the dynamic interaction between language and identity in digital environments and underscores the importance of critical language awareness. The findings contribute to sociolinguistic studies and offer insights for language education in adapting to digital communication trends.